The Effect of Leverage, Sales Growth, and Corporate Governance on Financial Distress in Property and Real Estate Sector Companies Listed on the IDX for the 2020-2024 Period - Musdeki Mulya; Khadijah Nurani (Indonesian Economic Review, 2026)
This study aims to examine the magnitude of the effect of leverage, sales growth, and corporate governance on financial distress in property and real estate sector companies listed on the Indonesia Stock Exchange during the 2020–2024 period. This research employs a quantitative approach using numerical data, starting from data collection to the presentation of research results, derived from secondary data in the form of companies’ financial statements for the 2020–2024 period. The sample consists of nine companies. Data analysis techniques include descriptive statistical analysis, classical assumption tests, panel data regression analysis, model selection tests using the Chow test, Hausman test, and Lagrange Multiplier test, hypothesis testing, and coefficient of determination analysis, conducted using EViews version 13. Based on the model selection results, the Random Effect Model is applied in this study. The findings indicate that, partially, leverage does not have a significant effect on financial distress, with a significance value of 0.7096 and a t-statistic of −0.374990. Sales growth has a significant effect on financial distress, with a significance value of 0.0023 and a t-statistic of 3.245622, indicating that changes in sales growth influence the financial distress condition of companies. Meanwhile, corporate governance does not have a significant effect on financial distress, with a significance value of 0.0924 and a t-statistic of 1.722942. Simultaneously, leverage, sales growth, and corporate governance have a significant effect on financial distress, with a significance value of 0.003637 and an F-statistic of 5.265885.